Change in the Anatomy of the Liver of Children in the Age Period (Eurasian Medical Research Periodical, 2023)
The purpose of the work is to study the topographic anatomy and macroscopic structure of the gallbladder and biliary tract in newborns, children and adolescents. Material and research methods. The object of the study was 54 corpses of newborns, children and adolescents of both sexes up to 16 еars old, with body weight from 3.0 kg to 55 kg, who died for reasons not related to pathology of the liver and bile ducts. Studied in detail the formation of the common bile duct, the options for its formation. Results. Age-related changes in the topography of the ducts concerned the length, diameter, depth, the number of branches and the severity of anastomoses between segmental branches and between the lobar ducts. The diameter of the common hepatic duct ranged from 1.1 mm to 5.0 mm, the right hepatic duct from 0.87 mm to 3.06 mm, and the left hepatic duct from 0.89 mm to 3.03 mm in different age groups. The length of the total hepatic duct is from 4.5 mm to 35.8 mm. When considering the angles of incidence between the common hepatic and left and right ducts varies. Conclusion. The results showed that in children of all age groups the formation of the common bile duct is variable; 2 to 5 intrahepatic ducts take part in its formation, while the number of ducts coming from the right lobe of the liver prevails.